Physics Learning Based on Practicum: Multi-meter - Murdani, Eka (Journal of Education and Vocational Research, 2015)
Teaching and learning activities effectively should be able to make students active for building their knowledge by placing the teacher as a facilitator. A step to make learning effectively is to organize a practicum. By practicum, students can develop their ability to think critically, analyze, and evaluate a problem. In this practicum has been done measuring of electrical quantities such as voltage by using a multimeter and resistance of resistor by reading color of the ring (color code) and by measuring directly of the resistor’s resistance by using multimeter. In this practicum students understand the use of a multimeter to measure the voltage and electrical resistance. The result of measurement for output voltage of DC power supply by using a multimeter is 3 V, 6 V, 9 V and 13 V. Has been made of series and parallel circuit for 3 resistors. The resistance value of each resistor is 2000 Ω same as relatively. The equivalent resistance for series circuit of 3 resistors is 6000 Ω and for parallel circuit is 700 Ω. The equivalent resistance is measured by using multimeter and has been made also for a combination circuit of series-parallel resistor.